Molecular Mechanisms Underlying Protective Role of Quercetin on Copper Sulfate-Induced Nephrotoxicity in Mice - Peng, Xinyan; Dai, Chongshan; Zhang, Min; Das Gupta, Subhajit (Frontiers in Veterinary Science, 2021)
Copper overload is an established cause of nephrotoxicity, but the precise molecular mechanism remains unknown. Our study aimed to investigate the molecular mechanism of copper sulfate (CuSO4)-induced nephrotoxicity and the protective effect of the natural compound quercetin using a mouse model. Mice were orally administered CuSO4 only (200 mg/kg per day), or co-administered CuSO4 (200 mg/kg per day) plus quercetin (25, 50 or 100 mg/kg per day), or quercetin only (100 mg/kg per day), or vehicle for 28 days. The blood and kidneys were collected for the examination of serum biomarkers, oxidative stress biomarkers, changes in histopathology and gene and protein expression. Our results show that quercetin supplementation attenuates CuSO4-induced renal dysfunction and tubular necrosis in a dose-dependent manner. Quercetin supplementation at 50 and 100 mg/kg significantly attenuated CuSO4-induced oxidative damage. Quercetin supplementation also inhibited the activities of caspases-9 and -3, and the expression of p53 and Bax mRNAs. Furthermore, quercetin supplementation markedly activated the expression of Nrf2 and HO-1 mRNAs, but inhibited the expression of NF-κB, IL-1β, IL-6, and TNF-α mRNAs. In conclusion, our results revealed that quercetin supplementation could inhibit CuSO4-induced nephrotoxicity in mice via the inhibition of mitochondrial apoptotic and NF-κB pathways and the activation of Nrf2/HO-1 pathway. Our study highlights quercetin as a promising candidate in treating copper overload-induced nephrotoxicity.